High prevalence and poor linkage to care of transfusion‐transmitted infections among blood donors in Dar‐es‐Salaam, Tanzania - Mohamed, Zameer (J Viral Hepat, 2019)
Blood transfusion is one of the most commonly relied upon therapies in sub‐Saharan Africa. Existing safeguards recommended include systematic screening for transfusion‐transmitted infections and restricted voluntary nonremunerated blood donor selection. We report the transfusion‐transmitted infection screening and notification practice at a large urban blood transfusion centre in Dar‐es‐Salaam, Tanzania. Between October 2016 and March 2017 anonymized records of all donors registered at the blood transfusion unit were accessed to retrospectively note demographic information, donor status, first‐time status, transfusion‐transmitted infection result and notification. 6402 consecutive donors were screened for transfusion‐transmitted infections; the majority were family/replacement blood donors (88.0%) and male (83.8%). Overall transfusion‐transmitted infections prevalence was 8.4% (95% CI 7.8‐9.1), with hepatitis B being the most prevalent infection (4.1% (95% CI 3.6‐4.6)). Transfusion‐transmitted infections were more common in family/replacement blood donors (9.0% (95% CI 8.3‐9.8)) as compared to voluntary nonremunerated blood donor (4.1% (95% CI 2.8‐5.7)). A minority of infected‐donors were notified of a positive result (8.5% (95% CI 6.3‐11.2)). Although transfusion‐transmitted infections are more prevalent among family/replacement blood donors, overall risk of transfusion‐transmitted infections across all groups is considerable. In addition, existing efforts to notify donors of a positive transfusion‐transmitted infection are poor. Future policies must focus on improving linkage to care for newly diagnosed patients with transfusion‐transmitted infections.